304 Lung cancer risk among hairdressers - a pooled analysis of case-control studies conducted between 1985 and 2010. (11th October 2013) - Olsson, A O; Xu,; Schüz,; Vlaanderen,; Kromhout,; Vermeulen,; Peters,; Pesch,; Brüning,; Straif,
Abstract : Objectives: Increased risk of lung cancer has been observed among hairdressers mostly in studies that did not adjust for smoking as a confounder; the objective of the present study was to evaluate this in the SYNERGY project while adjusting for smoking. Methods: SYNERGY consists of 16 pooled case-control studies conducted in Europe, Canada, China and New Zealand between 1985 and 2010. Lifetime occupational and smoking information was collected through interviews from 19, 369 cases of lung cancer and 23, 674 matched populations or hospital controls. Hairdressers were identified using the ISCO codes 5–70.20 (women's hairdresser) and 5–70.30 (men's hairdresser/barber). Odds ratios (ORs) and 95% confidence intervals (95% CI) of lung cancer risk were estimated using unconditional logistic regression. Results: Overall, 170 cases and 167 controls ever worked as hairdresser or barber. The ORs for lung cancer in male hairdressers/barbers were 1.04 (95% CI: 0.79, 1.37) before adjustment for smoking and 0.91 (95% CI: 0.66, 1.25) after, and did not change markedly with regard to the time of employment. The ORs in women were 1.65 (95% CI: 1.16, 2.35) before adjustment for smoking and 1.12 (95% CI: 0.75, 1.68) after; although women employed before 1954 experienced an increased lung cancer risk also after adjustment for smoking (OR 2.66, 95% CI: 1.09, 6.47). Smoking habits differed in female hairdressers vs. non-hairdressers, while there was no significant difference in smoking habits between male hairdressers/barbers and non-hairdressers/barbers. Conclusion: Our results suggest that most findings of increased lung cancer risk among hairdressers are likely due to smoking behaviour among this occupational group and not directly related to occupational exposure.